Influence of rare-earth based orthovanadate nanoparticles and cerium oxide on bioenergetic processes in mitochondria of hepatocytes - Аверченко, Е. А.; Кавок, Н. С.; Никитченко, Ю. В.; Клочков, В. К.; Малюкина, М. Ю.; Климов, С. А.; Ткачева, Е. Н.; Ефимова, С. Л. (Biophysical Bulletin, 1970)
The features of influence of newly synthesized nanoparticles (NPs) based on the rare earth elements, namely orthovanadates and cerium oxide, with the different geometrical parameters on the mitochondrial potential (ΔΨm) and respiration and oxidative phosphorylation of the liver were investigated. Reduction of ΔΨm, as well as the ATP level in isolated mitochondria under influence of orthovanadates and CeO2 (1-2 nm) NPs suggests that energy processes in the mitochondria are the target of the action of NPs. The highest inhibitory effect was shown by ekstrasmall spherical (orthovanadate and CeO2 of 1-2 nm) particles and only CeO2 with sizes of 8-10 nm have no a negative influence on all investigated parameters.